Pembuatan Media Infografis Melalui Pelatihan dan Pendampingan Desain Media Pembelajaran Berbasis Canva for Education Bagi Guru-guru SD di Kota Palembang - Patriot, Evelina Astra; Markos Siahaan, Sardianto; Cahaya Nurani, Dwi; Agung, Anugrah; Firansilady, Amanah; Kalsum, Umi; Nabilah, Riska; Sissy Lia, Risky (Jurnal Pengabdian Masyarakat Sains Indonesia, 2023)
In the current digital era, easy and fast access to information positively influences students' ability to access helpful information in the learning process. This service aims to increase teachers' capacity to design and produce products in the form of infographic learning media. The technological innovation trained in this service is to realize the development in electronic and printed form through Canva for education. Participatory Action Research (PAR) is the method used in the implementation of service activities with stages: 1) giving an initial test, 2) implementing the service, 3) the final stage consisting of evaluation and reflection, and 4) giving the final test. The target participants of the service activities were elementary school teachers of science subjects in Palembang City. Based on the data obtained, there is an increase in test results with an N-gain of 0.81, which is included in the high category. Based on the above results, the training participants strongly agree that this service activity can increase their understanding and skills in creating infographic learning media through Canva for Education